(untitled) (Revista Científica Compendium, 2020)
The management system is required in a business to achieve exceptional results. It is made up of three components: the strategic, tactical and operational ones. In turn, the components consist of: strategic, improvement, innovation, flow, project and daily management. The use of the PDCA management method, in each component, makes it unique, independent of the trade names given by consulting companies worldwide.